Pengaruh Iklim Organisasi, Fasilitas Belajar dan Kompetensi IT terhadap Kinerja Guru SMK Setia Bhakti Tangerang Di Masa Pandemi Covid 19 - Lewaherilla, Meyke (Ridwan Institute, 2021)
The Covid 19 pandemic is a condition that has a profound impact on all industries in Indonesia and of course also has an impact on educational organizations, one of which is SMK Setia Bhakti Tangerang. The purpose of this study was to determine teacher performance during the Covid 19 pandemic. Many factors affect teacher performance including organizational climate, learning facilities and IT competencies, where teachers must feel comfortable describing their work environment. Equipped with learning facilities as a means of infrastructure, of course, can support teacher performance on the other hand by having IT competencies, literacy in technology will be an added value for teachers because IT is very useful to support teacher performance. The research method that the author uses is the quantitative method by using a questionnaire to 34 teachers of SMK Setia Bhakti. From the research results, it was found that there was a positive relationship between organizational climate and teacher performance, learning facilities and performance, IT competence and performance.